2017
DOI: 10.1080/14397595.2017.1366005
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of the Sauvé–Kapandji procedure for distal radioulnar joint disorder with rheumatoid arthritis or osteoarthritis: Results of one-year follow-up

Abstract: The Sauvé-Kapandji procedure for treating disorders of the distal radioulnar joint DRUJ showed good results clinically and radiographically, irrespective of RA or OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
1
11
0
2
Order By: Relevance
“…On the contrary, many previous reports showed that the arc of wrist motion, especially in wrist flexion, does not improve or decreases postoperatively. [1][2][3][4][5][6][7][8][9] The reason why the arc of wrist motion worsens after the S-K procedure is not fully understood. Some possible reasons for dorsal soft tissue contracture caused by intra-articular invasion of the wrist are as follows: synovectomy, extensor tendon adhesion due to duration of postoperative immobilization of the wrist, or fixation of the DRUJ with a screw.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, many previous reports showed that the arc of wrist motion, especially in wrist flexion, does not improve or decreases postoperatively. [1][2][3][4][5][6][7][8][9] The reason why the arc of wrist motion worsens after the S-K procedure is not fully understood. Some possible reasons for dorsal soft tissue contracture caused by intra-articular invasion of the wrist are as follows: synovectomy, extensor tendon adhesion due to duration of postoperative immobilization of the wrist, or fixation of the DRUJ with a screw.…”
mentioning
confidence: 99%
“…Therefore, little is known about the pre-and postoperative ROM after the S-K procedure without tendon rupture, especially in RA patients, while many studies have reported ROM with tendon rupture. [1][2][3][4][5][6][7][8][9] Furthermore, comparison of pre-and postoperative ROM between the S-K and Darrach procedures without tendon rupture has not been discussed widely.…”
mentioning
confidence: 99%
“…Uma das melhores indicações para a técnica S-K é a impactação ulnocarpal de uma longa ulna secundária a uma fratura do rádio distal. Esta técnica permite a correção do comprimento ulnar preservando os ligamentos CFCT e ulnocarpal (MINAMI et al, 2018;IKEDA et al, 2018;LICHTMAN et al, 1998).…”
Section: 3lesões Da Arudunclassified
“…A técnica S-K também é indicada para o tratamento de instabilidades isoladas da ARUD secundárias a rupturas ligamentares. As técnicas de reparo do ligamento nem sempre oferecem adequada estabilidade articular e exigem longos períodos de imobilização do punho e do cotovelo, que são muito desconfortáveis e incapacitantes para o paciente e, em alguns casos, levam à perda da rotação do antebraço (MINAMI et al, 2018;IKEDA et al, 2018;LICHTMAN et al, 1998 (MINAMI et al, 2018;IKEDA et al, 2018;LICHTMAN et al, 1998;ALNOT et al, 1995;OBRY et al, 1996).…”
Section: 3lesões Da Arudunclassified
See 1 more Smart Citation